A possible amendment to the criminal procedure and evidence act, 1939 of the republic of Botswana with regard to plea and sentence agreements in an effort to promote the expeditious and efficient disposition of criminal matters - Curlewis, Llewelyn Gray (University of Pretoria, 2020)
Mini Dissertation (LLM)--University of Pretoria, 2019.